Emerging Opportunities: Monitoring and Evaluation in a Tech-Enabled Wo rld - Raftree, Linda; Bamberger, Michael (ITAD & Rockefeller Foundation, 2014)
Monitoring and evaluation practice is using information and communicat ion technologies for more timely data, and more inclusive voice and fe edback.